2001
DOI: 10.1093/aje/154.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Impact of Long-term Wartime Stressors on Mortality among the Middle-aged and Older Population in Beirut, Lebanon, 1983-1993

Abstract: The authors investigated the relation between exposure to wartime events and cardiovascular disease (CVD) and all-cause mortality in Lebanon, which recently underwent a 16-year civil war. The study population comprised a representative cohort (n = 1,786) of middle-aged and older men and women who, in 1983, participated in a community-based health interview survey. In 1993, the authors traced 87.7 % of the original cohort (n = 1,567) and assessed their vital status, exposure to war-related events, and, in case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
2
37
1
Order By: Relevance
“…These findings were consistent in sensitivity analyses in which a more-inclusive definition of exposure to the Nazi regime was used and those exposed were subdivided into those with exposure suggesting moderate trauma and those with exposure suggesting severe trauma. Although some studies have found a greater mortality risk associated with traumatic events in non-Jewish Norwegian concentration camp survivors 4 and in other civilian and military groups exposed to traumatic events, 3,15 the findings of the current study add to a more-recent body of research that suggests that early-life exposure to severe psychological trauma does not pose a greater mortality risk in later life. 5,6 Despite physical vulnerability and well-documented emotional vulnerability, [16][17][18] this group of survivors of the Nazi regime is not at greater risk for mortality than the general population of older adults.…”
Section: Discussioncontrasting
confidence: 42%
“…These findings were consistent in sensitivity analyses in which a more-inclusive definition of exposure to the Nazi regime was used and those exposed were subdivided into those with exposure suggesting moderate trauma and those with exposure suggesting severe trauma. Although some studies have found a greater mortality risk associated with traumatic events in non-Jewish Norwegian concentration camp survivors 4 and in other civilian and military groups exposed to traumatic events, 3,15 the findings of the current study add to a more-recent body of research that suggests that early-life exposure to severe psychological trauma does not pose a greater mortality risk in later life. 5,6 Despite physical vulnerability and well-documented emotional vulnerability, [16][17][18] this group of survivors of the Nazi regime is not at greater risk for mortality than the general population of older adults.…”
Section: Discussioncontrasting
confidence: 42%
“…A longitudinal study of traumatic stress resulting from prolonged war in Beirut found that individuals with more war-related traumatic experiences were at greater risk for CVD-related mortality. The relationship between trauma and CVD differed by gender such that CVD-related mortality was more evident in women who suffered personal traumas, such as injuries or family deaths, while it was more prominent in men who had suffered property loss, work-related problems, or displacement from home (9). In a study of cardiovascular morbidity in World War II prisoners of war, increased risk of CVD was present in those who developed PTSD (10).…”
Section: Cardiovascular and Metabolic Morbidity/mortality In Ptsdmentioning
confidence: 99%
“…15 Furthermore, and because of the age-selection criteria imposed on the subjects included in the analysis (over 65 years), our findings are more likely to reflect an examination of period effect concurring with the war atrocities than a cohort effect of early environmental exposures. At the time this report was completed (July 2006) the country was ravaged by another war, resulting in over 1180 deaths and around 4500 wounded, nearly all civilians.…”
Section: -1990 Femalesmentioning
confidence: 83%